Single-molecule quantification of 5-hydroxymethylcytosine for diagnosis of blood and colon cancers - Noa Gilat (Clinical Epigenetics, 2017)
Abstract Background The DNA modification 5-hydroxymethylcytosine (5hmC) is now referred to as the sixth base of DNA with evidence of tissue-specific patterns and correlation with gene regulation and expression. This epigenetic mark was recently reported as a potential biomarker for multiple types of cancer, but its application in the clinic is limited by the utility of recent 5hmC quantification assays. We use a recently developed, ultra-sensitive, fluorescence-based single-molecule method for global quantification of 5hmC in genomic DNA. The high sensitivity of the method gives access to precise quantification of extremely low 5hmC levels common in many cancers. Methods We assessed 5hmC levels in DNA extracted from a set of colon and blood cancer samples and compared 5hmC levels with healthy controls, in a single-molecule approach. Results Using our method, we observed a significantly reduced level of 5hmC in blood and colon cancers and could distinguish between colon tumor and colon tissue adjacent to the tumor based on the global levels of this molecular biomarker. Conclusions Single-molecule detection of 5hmC allows distinguishing between malignant and healthy tissue in clinically relevant and accessible tissue such as blood and colon. The presented method outperforms current commercially available quantification kits and may potentially be developed into a widely used, 5hmC quantification assay for research and clinical diagnostics. Furthermore, using this method, we confirm that 5hmC is a good molecular biomarker for diagnosing colon and various types of blood cancer.